A case study on perceived feasibility of natural farming of ginger at Ri-Bhoi District, Meghalaya - Rishikesh Kumar; Rajkumar Josmee Singh (Umiam ; CPGSAS, CAU, 2023)
Green revolution has significantly increased agricultural production through the use of fertilizers and agrochemicals. However, this agricultural intensification contributed much towards negative environmental issues such as global warming, eutrophication of water systems and soil degradation etc. Natural farming is a unique chemical residual free farming method that is considered to be diversified farming system, which integrates crops, trees and livestock, allowing functional biodiversity. Prevalence of favorable agro-climate and wealth of traditional knowledge on cultivation of Rhizome crops (especially Ginger) give ample scopes for taking Keeping the above facts in view, the following research objectives have been formulated for the study, viz., (1) To assess the perception on natural farming of ginger by the farmers; and (2) To perform feasibility analysis of natural farming of ginger. The study followed descriptive research design and purposive sampling technique. A sample of 30 respondents each from the three villages viz., (i) Thadnongiaw, (2) Kdonghulu, and (3) Liarkhla of C&RD Block, Bhoirymbong of Ri-Bhoi district have been purposively selected in order to constitute a total of ninety (90) respondents in the study. The study revealed that more than fifty percent (52.23 %) of the respondents belonged to middle age category. Highest percentage of 31.11 % of respondents had education below class X std; highest percentage of 43.33 % of respondents were small farmers. Majority of respondents (i.e. 66.66 %) had medium level of farming experience. About fifty percent of the respondents had high agricultural diversification (52.23 %) and low cropping intensity (51.11%). Highest percentage of 37.77 % of respondents had medium level of decision-making. More than forty percent of respondents (44.44%) of respondents had medium ability to cope up with change. Majority of respondents (58.88%) belonged to medium level of perception on natural farming. Analysis on future wheel technique revealed that very high percentage of about eighty three percent (83.34%) of the respondents perceived the Natural Farming is feasible owing to its sustainability.
Keywords: Ginger -- Natural farming -- Meghalaya